Improving Arabic Speaking Skills through HelloTalk in a Southern Thai Islamic School - Nafisah Rohmatul Ummah; Syamsul Anam; Mokhammad Miftakhul (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study examined the implementation and effectiveness of HelloTalk in improving Arabic speaking skills among eighth-grade students at Ban Yaning Islamic School, Narathiwat, Thailand. A quantitative pre-experimental design with a one-group pretest–posttest model was employed, involving 30 students selected purposively. Data were collected through speaking tests, observation, interviews, and documentation, while speaking performance was assessed through pronunciation, grammar, vocabulary, fluency, and comprehension. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, the Wilcoxon signed-rank test, and N-Gain analysis. The results showed that students’ mean score increased from 49.67 in the pretest to 77.33 in the posttest, with a Wilcoxon significance value of 0.000, indicating a statistically significant improvement. However, the N-Gain score of 18.83% indicated low practical effectiveness. This study implies that HelloTalk can support Arabic speaking practice as a supplementary medium, but its use should be strengthened through structured teacher guidance, stable internet access, sufficient implementation time, and communicative speaking tasks.